Fabry disease: a disorder of childhood onset - Schiffmann, Raphael; Ries, Markus (Pediatric neurology, 2016)
Fabry disease, an X-linked disorder of glycosphingolipids, markedly increases the risk of systemic vasculopathy, ischemic stroke, small-fiber peripheral neuropathy, cardiac dysfunction, and chronic kidney disease. We performed an extensive PubMed search on the topic of Fabry disease and drew from our cumulative 43 years of experience. Most of these complications are nonspecific in nature and clinically indistinguishable from similar abnormalities that occur in the context of more common disorders in the general population. This disease is caused by variants of the GLA gene, and its incidence may have been underestimated. However, one must also guard against overdiagnosis of Fabry disease and unjustified enzyme replacement therapy, because some of the gene variants are benign. Specific therapy for Fabry disease has been developed in the last few years, but its clinical effect has been modest. Novel therapeutic agents are being developed. Standard “nonspecific” medical and surgical therapy is necessary and effective in slowing deterioration or compensating for organ failure in patients with Fabry disease. Fabry disease is a treatable and modifiable genetic risk factor for a myriad of clinical organ complications. Fabry disease may be frequently overlooked but on occasion overdiagnosed.